2006
DOI: 10.1534/genetics.105.052019
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Human Immunodeficiency Virus Envelope Gene Is Dominated by Purifying Selection

Abstract: The evolution of the human immunodeficiency virus (HIV-1) during chronic infection involves the rapid, continuous turnover of genetic diversity. However, the role of natural selection, relative to random genetic drift, in governing this process is unclear. We tested a stochastic model of genetic drift using partial envelope sequences sampled longitudinally in 28 infected children. In each case the Bayesian posterior (empirical) distribution of coalescent genealogies was estimated using Markov chain Monte Carlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 71 publications
4
58
0
Order By: Relevance
“…The high mutation rate of HIV is expected to lead to a considerable deleterious mutation load in the viral population, such that the most recent mutations, segregating on external branches of HIV phylogenies, are likely to be deleterious [28,29]. This effect is present in each of the nine patients analyzed; mean substitution rates were consistently higher for external branches than for internal branches (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The high mutation rate of HIV is expected to lead to a considerable deleterious mutation load in the viral population, such that the most recent mutations, segregating on external branches of HIV phylogenies, are likely to be deleterious [28,29]. This effect is present in each of the nine patients analyzed; mean substitution rates were consistently higher for external branches than for internal branches (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A natural solution to this problem would be to fit exponential functions between consecutive time points. More importantly, however, selective responses to the host immune system are known to be an important evolutionary factor (Edwards et al 2006;Lemey et al 2006), having an effect on intrahost genealogies that is not fully captured merely by adjusting the effective population size. Other commonly used methods such as BEAST (Drummond et al 2002(Drummond et al , 2005(Drummond et al , 2012Drummond and Rambaut 2007;Minin et al 2008) also ignore the effects of selection on genealogies (as well as ignoring recombination); thus, developing methods that can robustly account for both selection and recombination (and indeed other factors) remains a challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the genetic diversity within a single infection can be very high. Important clinical variables, such as the rate of progression to AIDS and the set point viral load, are related to the diversity and evolution of the within-patient viral population (Shankarappa et al 1999;Ross and Rodrigo 2002;Williamson 2003;Edwards et al 2006;Lemey et al 2007;Pybus and Rambaut 2009), and so genetic data from these populations are of medical relevance in addition to providing insight into molecular evolutionary processes. However, population genomic inference from HIV sequence data can be challenging as result of high rates of mutation and recombination within a small RNA genome of $10 kb.…”
mentioning
confidence: 99%
“…Numerous studies have reported PGIM patterns consistent with slightly deleterious amino acid changes. Excess rare polymorphisms and higher r pd for nonsynonymous compared to synonymous variation appear to be general patterns in viral (Edwards et al 2006;Pybus et al 2006;Hughes 2009) and bacterial genomes (Hughes 2005;Charlesworth and Eyre-Walker 2006;Rocha et al 2006;Hughes et al 2008) as well as in animal mtDNA (Ballard and Kreitman 1994;Nachman et al 1996;Rand and Kann 1996;Hasegawa et al 1998;Wise et al 1998;Weinreich and Rand 2000;Gerber et al 2001;Subramanian et al 2009). Similar patterns have been noted in nuclear genes from yeast (Doniger et al 2008;Liti et al 2009), Drosophila (Akashi 1996;Fay et al 2002;Loewe et al 2006;Andolfatto et al 2011), humans (Cargill et al 1999;Sunyaev et al 2000;Hughes et al 2003;Williamson et al 2005;Boyko et al 2008;Keightley and Halligan 2011;Subramanian 2012), mice (Halligan et al 2010), and plants (Bustamante et al 2002;Nordborg et al 2005;Foxe et al 2008;Fujimoto et al 2008;Gossmann et al 2010;Branca et al 2011;.…”
Section: Within-lineage Contrasts Of Polymorphism and Divergencementioning
confidence: 99%